(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Supraclavicular brachial plexus block is a commonly used regional anaesthetic technique for upper limb surgeries. The addition of adjuvants to local anaesthetics is known to improve block characteristics and prolong postoperative analgesia. This study was designed to compare dexamethasone and dexmedetomidine as adjuvants to ropivacaine. Methodology: This prospective randomized double-blind study was conducted in 108 patients undergoing upper limb surgeries. Patients were randomly allocated into two groups: Group A received 0.5% ropivacaine with dexamethasone and Group B received 0.5% ropivacaine with dexmedetomidine for supraclavicular brachial plexus block under ultrasound guidance. Onset and duration of sensory and motor block, duration of analgesia, haemodynamic parameters, sedation, and adverse effects were assessed. Statistical analysis was performed using SPSS software, and p-value <0.05 was considered significant. Results: Group a showed significantly faster onset of sensory and motor block compared to Group B. The duration of sensory and motor blockade and total duration of analgesia were significantly longer in Group A. Time to first rescue analgesic was also prolonged in Group A. Sedation was observed only in Group B. Haemodynamic parameters and adverse effects were comparable between both groups. Conclusion: Dexamethasone is a more effective adjuvant than dexmedetomidine to ropivacaine in supraclavicular brachial plexus block, providing faster onset and prolonged analgesia with minimal side effects.